(untitled) (Applied Biological Research, 2012)
The present study was aimed to microscopically assess dimorphism in nuclear polyhedrosis virus (BmNPV) responsible for ‘Grasserie’ disease in silkworm, Bombyx mori L. Tissue sections of infected larvae integument were found ruptured, had abundant lump cells and released milky fluid containing occluded bodies (OBs). Nuclei of columnar epithelial cells of integument were almost covered with BmNPV polyhedra. Scanning electron micrograph (SEM) revealed full lesions in infected integuments with very fragile hypo dermis. Transmission electron micrograph (TEM) showed that infecteddifferent parts of peripheral membrane contain lipid globules started to diffuse continuously to form a large structure to occupy maximum OBs. In advanced stage of infection, two viral phenotypes were noticed. 1st form occluded within polyhedra was responsible for primary infection in mid-gut cells. The 2nd form ‘budded virus (BV)’ never became occluded and was released into haemolymph and spread infection bycell to cell contact within insect body. The fully transformed lipid globules discharged the 1st form whereas BV was observed in integument, mid gut and Malpighian tissues. Interestingly, the infected mid gut cells were dilated in presence of OBs and gradually increased in number to form chain-like structure which broke up no sooner the number of OBs reached highest carrying capacity, releasing polyhedra in gut juice. Inner layer of infected Malpighian tissues were loose and fragmented with OBs in between the striations of Malphigian cells. BVs, the new finding from B. mori, are responsible for virulence of BmNPV in silkworm. 29 and 17 kDa proteins in multivoltine (Nistari) and bivoltine (NB4D2), respectively, were absent in the haemolymph of BmNPV infected counterpart. The total quantity of haemolymph protein was more in multivoltine samples than in bivoltine samples.